Ações coletivas civis na atualidade: dos programas de responsabilidade/compromisso social às redes de movimentos sociais - Maria da Glória Gohn (Ciências Sociais Unisinos)
This paper focuses on the protagonism of the civil society by addressing the theme of the civil collective actions. Therefore, some conceptual presuppositions should be explained allowing that the subjects, and the character of these actions to be known and understood in the analysis. This is the initial task of the text that aims to name and to contemplate the main structural forms of the civil collective actions in contemporary Brazil, highlighting the social movements and the NGOs (Non-Governmental Organizations).